Pembelajaran Menggunakan Media Gambar Huruf Alfabet A-J Pada Anak Tunagrahita Ringan di SLB Theresia Sonder - Anna Zega (Jurnal Ilmiah Wahana Pendidikan, 2022)
Children with special needs are children who have limitations or barriers both physically and intellectually. Children with mental retardation are one of the children with special needs who are included in the group of children with mental disabilities with intellectual abilities below the average, low thinking ability, weak attention and memory, difficulty in abstract thinking, and inability to think logically. One of the solutions that can be used is Learning to Use the A-J Alphabet Picture Media. Therefore, the purpose of this research is to recognize the letters of the alphabet by using image media. The research method used is experimental research with a Single Subject (SSR) design. The results of the study were obtained for 20 sessions where each session there was an increase from 26% to 94% of extraordinary achievements that students could achieve even though in a not fast time. Based on the results of the study, it can be concluded that the use of media images of the letters of the A-J alphabet is very effective in increasing the ability to recognize letters of the alphabet A-J in mild mentally retarded students at Theresia Sonder Special School